2023
DOI: 10.3390/v15010218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Human Mesenchymal Stromal Cells as Carriers for the Delivery of Oncolytic HAdV-5 to Head and Neck Squamous Cell Carcinomas

Abstract: Human multipotent mesenchymal stromal cells (hMSCs) are of significant therapeutic interest due to their ability to deliver oncolytic adenoviruses to tumors. This approach is also investigated for targeting head and neck squamous cell carcinomas (HNSCCs). HAdV-5-HexPos3, a recently reported capsid-modified vector based on human adenovirus type 5 (HAdV-5), showed strongly improved infection of both hMSCs and the HNSCC cell line UM-SCC-11B. Given that, we generated life cycle-unmodified and -modified replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…They demonstrated these MSCs shielded-OA effectively targeted to tumor in many xenografted mouse models after local or systemic administration. 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 A study demonstrated that, after intra-arterial injection, human-derived MSC-loaded OA DNX-2401 can selectively deliver the virus to tumor site of glioma in mice and exert oncolytic effects. 100 Recently, the same team has demonstrated that perfusion-guided endovascular super-selective intra-arterial infusion of MSC-loaded DNX-2401 was safe in humans.…”
Section: Scsmentioning
confidence: 99%
“…They demonstrated these MSCs shielded-OA effectively targeted to tumor in many xenografted mouse models after local or systemic administration. 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 A study demonstrated that, after intra-arterial injection, human-derived MSC-loaded OA DNX-2401 can selectively deliver the virus to tumor site of glioma in mice and exert oncolytic effects. 100 Recently, the same team has demonstrated that perfusion-guided endovascular super-selective intra-arterial infusion of MSC-loaded DNX-2401 was safe in humans.…”
Section: Scsmentioning
confidence: 99%
“…Lung and pancreatic adenocarcinoma, melanoma IP [161] Men-MSCs + PBMNCs Lung adenocarcinoma, epidermoid carcinoma, pharynx squamous cell carcinoma IP [162] Ad-ICOVIR15, Ad-ICOVIR15-cBITE Men-MSCs Lung adenocarcinoma and epidermoid carcinoma IP [163] Ad-ICOVIR15, Ad-ICOVIR17 AT-MSCs Glioblastoma multiforme IT, IV [164] Ad-ICOCAV17 AT-MSCs Osteosarcoma and brain tumours IV [165] Spontaneous lung carcinoma IV [166] Ad-hOC-E1 BM-MSCs Renal carcinoma IP [167] Ad-RLX-PCDP BM-MSCs Pancreatic cancer IV [168] Ad-Ad5-HexPos3 BM-MSCs, AT-MSCs Head and neck squamous cells carcinoma IV, IP [169] Ad-Ad5-Ki67/IL-15 Source of MSCs non-specified Glioblastoma multiforme IT [170] Ad-5, Ad-3, Ad-5.Pk7-Delta24…”
Section: Men-mscs Bm-mscsmentioning
confidence: 99%